Effect of isthmic and ampullary oviductal proteins on lipid peroxidation levels of buffalo spermatozoa - KUMARESAN, A; ANSARI, M R; GARG, ABHISHEK; KATARIA, MEENA (The Indian Journal of Animal Reproduction, 2023)
A study was undertaken to find out the effect of oviductal proteins from different regions of oviduct and phases ofestrous cycle on lipid peroxidation (LPO) of buffalo spennatozoa. Oviducts were collected from apparently healthy buffalogenital tracts (nonluteal and luteal phases of estrous cycle) and separated into isthmus and ampulla. Each segment of oviduct(nonluteal and luteal) was flushed with PBS (pH 7.4), centrifuged, filtered and frozen at -20°C. Proteins in pooled nonlutealisthmic and ampullary and luteal isthmic and ampullary fluids were precipitated overnight using ammonium sulphate, centrifugedand dialyzed (> JOkDa). Aliquots of IO mg proteins were lyophilized in cryovials and stored at -20°C. Pooled goodquality ejaculates (n=6) from two Murrah buffalo bulls were utilized for the study. Each pooled ejaculate was split into fiveparts, extended in Tris-Egg Yolk-Citrate extender and cryopreserved in 0.5 ml French straws at -I 96°C. Before freezing, theisthmic and ampullary (luteal and nonluteal) oviductal proteins were supplemented ( I mg per ml). Random semen straws fromeach group were evaluated for LPO levels in sperm and seminal plasma in equilibrated and frozen thawed semen. Resultsrevealed that addition ofnonluteal isthmic oviductal proteins reduced the LPO level in post thaw spermatozoa significantly(p
Keywords: Buffalo; oviductal proteins; Spermatozoa; lipid peroxidation